Clinically unrecognized plasma volume expansion predicts long‐term all‐cause‐mortality in chronic heart failure. Issue 10 (3rd August 2022) - Ahlgrim, Christoph; Seiler, Florian; Birkner, Philipp; Schoechlin, Simon; Grundmann, Sebastian; Bode, Christoph; Pottgiesser, Torben
Abstract: Introduction: Chronic heart failure (CHF) is associated with elevated total blood volume (BV) and distinct phenotypes of total red cell volume (RCV) and plasma volume (PV) elevations. Especially PV expansion during clinical decompensation is linked with adverse clinical outcomes. The role of PV expansion in compensated CHF patients is less clear. Aim of the present study is to investigate the impact of BV parameters on long‐term mortality in CHF patients investigated at a compensated state. Methods and Results: BV, PV and RCV were determined in 44 (9 female) compensated CHF patients using an abbreviated carbon monoxide method, who were followed up for 6.0 years, (range: 3.7–6.5 years) for all‐cause mortality. In univariate analysis PV expansion but not BV and RCV predicted all‐cause mortality ( p  = .021). A cutoff of 1800 ml PV/m² body‐surface area allows stratification for all‐cause mortality ( p  = .044). PV expansion but not RCV reduction explains the significantly lower hematocrit values of nonsurvivors. Discussion: In this pilot study, PV expansion, which was unnoticed from a clinician's perspective, but is indicated by significantly lower hematocrit, appears to be a relevant predictor of long‐term all‐cause mortality. Whether PV expansion constitutes an adverse CHF phenotype and can be targeted by diuretic therapy is currently unclear.